Upaya Meningkatkan Kualitas Spiritual Generasi Penerus Guna Mewujudkan Desa yang Bermartabat di Desa Perkebunan Pulahan - Arifin Marpaung; Siti Nuraini As’ari Putri; Roudati Jannah; Wirdayanti Sihombing; Dini Ulya Sarah Samosir; Khairun Nisa; Nirleka Nasution; Dio Azril Alfahri; Farhan Aulia Nasution9 (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The next generation needs to be considered because this is an important aspects as a determinant of the continuity of human life. To make it happen, they must be taught about all forms of worship that have a long-term orientation. Thus, the next generation of quality is formed for the next human resources. KKN is a student lecture activity outside the classroom as a form of community development as well as a place to develop the knowlegde that has been obtained from the university. KKN is also a forum for students to train themselves to be ready to enter the community. Because students are an important part in efforts to educate people who believe in divinity Keywords: Next Generation, Community Service, Religion